Pengembangan Perangkat Pembelajaran Berorientasi Model Pembelajaran Kooperatif Tipe Jigsaw: Tinjauan Proses dan Hasil Belajar - Yusuf Yusuf; Suhirman Suhirman; M. Harja Efendi; Yuliana Wahyu (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to develop a jigsaw cooperative learning-oriented learning tool, then see its impact on the process and student learning outcomes of biology. The development adopts the Morrison, Ross, & Kemp (2010) model, which consists of nine stages and ends with field trials to produce teaching materials, teacher guides, lesson plans, LKPD, and test questions. Trial I was carried out on grade X MA Darun Najah Duman, to produce draft 1 learning tools and validate research instruments. Trial II on students of MA Putri NW Narmada. Measured aspects of the learning process include: observing the ability of teachers to apply learning tools, teacher and student activities, student cooperative skills, and capturing student responses with questionnaires. Learning outcomes are shown from the final test score. Testing using a one-group pretest-posttest design. Data from observations and questionnaires were analyzed using descriptive statistics and test score data were analyzed using the t one-sample test statistic using SPSS 16.0 for Windows. The results showed that the tools developed were able to be applied by teachers, increased teacher and student activities, encouraged students to do positive activities in learning, and accustomed students to cooperative skills. Students are happy with learning, so that learning that applies a jigsaw cooperative learning model-oriented device has a significant effect on the achievement of the minimum completeness criteria of students (μ = 78, μ0 = 67, t = 6,800, p = .000 <.005) The learning tools developed are suitable for use in biology learning at madrasah aliyah in Islamic boarding schools.